PENYELESAIAN PROBLEMATIKA WALI MAFQUD - Hilmi, Muhammad; Misnanto (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2023)
Wali mafqud is the guardian of the unknown bride whereabouts so do not know whether it is dead or still alive. As happened in the village of wotgalih, there are women who live wandering since childhood by his parents, until now his whereabouts are unknown his father only the latest news is in Malang. Therefore, it is very It is important to clarify because the marriage guardian can determine whether a marriage is legal or not marriage. The formulation of the problem in this study is: What are the causes the occurrence of the mafqud guardian problem and efforts to solve it at the office Religious Affairs (KUA) Yosowilangun District, Lumajang Regency? What is the positive legal perspective on solving Wali problems Mafqud at the Office of Religious Affairs (KUA) District Yosowilangun Regency Lumajang? Writing this thesis includes the type of field research (empirical juridical), with a case study approach, with interview data collection techniques, observation, and documentation. This research belongs to the type of qualitative research. The data sources used are primary sources including the head of KUA, penghulu and secondary include photos, transcripts of interview guidelines, recordings, through purposive and time sumpling techniques. While the analysis stage data is done by editing, classification, verification, conclusion, and analysis. The validity of the data applied is credibility, dependability, and reliability confirmability. The results of this study are first: the causes of mafqud guardians include: there is a divorce then there is no communication anymore, because both parents married overseas and then left again and left their children, his father migrated after several years lost communication and did not known whereabouts, and raised orphans. The solution carried out by the Office of Religious Affairs (KUA) Yosowilangun against the bride and groom whose guardian is mafqud, that is, ordering the bride and groom to face the village head to explain that his guardian's whereabouts are unknown and witnessed by two people. Then the stamped statement letter along with the other files are given to modin to register marriage to the Affairs Office Yosowilangun Religion. After that, it will be investigated first by the KUA so that there is no manipulation of data related to mafqud guardians. Second: Wali mafqud di explained in the Regulation of the Minister of Religion no. 20 of 2019 article 13 paragraph 5 that the bride and her family go to the village head to request a stamped statement and be witnessed by two witnesses, after it was given to modin to be used as a registration requirement at KUA.